Indication for thoracotomy - Chifflet, Juan (Cirugía del Uruguay, 1990)
In the polytraumatized it is necessary and essential conduct continuous reevaluations to achieve diagnoses of injuries that may occur at the beginning unnoticed and be a reason for surgical solutions (94, 95, 96).